2019
DOI: 10.18502/ijm.v11i2.1073
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microorganisms in persistent/secondary endodontic infections with respect to clinical and radiographic findings: bacterial culture and molecular detection

Abstract: Background and Objectives: Bacterial agents are commonly accepted as the main etiology of endodontic infections. A significant proportion of oral bacteria cannot be cultured using existing methods. Since diversity and abundance of bacterial species are different in different populations, the present study was aimed to identify effective microorganisms in persistent endodontic infections in Iranian patients based on culture and molecular biology methods using sequence analysis of 16S rDNA gene. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
(69 reference statements)
0
17
0
1
Order By: Relevance
“…Candida albicans is the most common prevalent fungus in the root canals of infected teeth. Recent studies have also proved the role of viruses such as Cytomegalovirus (CMV) and Epstein–Barr virus (EBV) in symptomatic periapical lesions [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Candida albicans is the most common prevalent fungus in the root canals of infected teeth. Recent studies have also proved the role of viruses such as Cytomegalovirus (CMV) and Epstein–Barr virus (EBV) in symptomatic periapical lesions [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used E. faecalis as a model organism since it is the most common bacterial species recovered in secondary apical periodontitis (Zargar et al, 2019). Although not shown in this manuscript, the same approach should also work for other Grampositive or Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have only focused on detecting the presence of resistance genes in different oral environments, including bacteria isolated from different types of endodontic infections [35,36]. Other studies have only been dedicated to associate the presence of certain bacterial species with the presence of clinical symptoms [37]. The only study similar to ours that we found during the review of the literature is that of De Lima et al In this study, the authors only analyzed the association between the presence of lactamic resistance genes (blaTEM) and clinical parameters (pulpal diagnosis, sinus tract, pain, and swelling); but they found no association between these variables [38].…”
Section: Discussionmentioning
confidence: 99%